2008
DOI: 10.3144/expresspolymlett.2008.87
|View full text |Cite
|
Sign up to set email alerts
|

Multi-walled carbon nanotube filled polypropylene nanocomposites based on masterbatch route: Improvement of dispersion and mechanical properties through PP-g-MA addition

Abstract: Abstract. Multi-wall carbon nanotubes (MWNTs) filled polypropylene (PP) nanocomposites were prepared through diluting a PP/MWNT masterbatch in a PP matrix by melt compounding with a twin screw extruder. Polypropylene grafted maleic anhydride (PP-g-MA) was used to promote the carbon nanotubes dispersion. The effect of PP-g-MA addition on the rheological, mechanical and morphological properties of the nanocomposites was assessed for different MWNTs loadings. Scanning electron microscopy (SEM) has shown that nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
143
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(154 citation statements)
references
References 29 publications
10
143
0
1
Order By: Relevance
“…Mouritz et al [31] also reported that EP/GF composite laminates exhibited a relatively low mechanical performance with the flexural strength of 212MPa and flexural modulus of 12.9 GPa, with the fiber volume of 34%. Generally, mechanical properties of polymer/GF composite laminates depended on the properties of each primary component, the nature of the interface, and the locus of filler-matrix interaction between the matrix resins and GFs [32]. In our BA-ph/BPA/ GF systems, the good mechanical properties could be attributed to multiple factors.…”
Section: Mechanical Properties Of Ba-ph/bpa/gfmentioning
confidence: 80%
“…Mouritz et al [31] also reported that EP/GF composite laminates exhibited a relatively low mechanical performance with the flexural strength of 212MPa and flexural modulus of 12.9 GPa, with the fiber volume of 34%. Generally, mechanical properties of polymer/GF composite laminates depended on the properties of each primary component, the nature of the interface, and the locus of filler-matrix interaction between the matrix resins and GFs [32]. In our BA-ph/BPA/ GF systems, the good mechanical properties could be attributed to multiple factors.…”
Section: Mechanical Properties Of Ba-ph/bpa/gfmentioning
confidence: 80%
“…Strong coupling between filler and matrix is particularly difficult to achieve with non-polar polymers like polyethylene and polypropylene. Chemical compatibility of nanofiller and polyolefin matrix has been enhanced and the dispersion of nanofiller improved through the addition of polymeric compatibilizers such as maleic anhydride grafted polymers [8][9][10]. Yang et al [8] enhanced the compatibility and dispersion of MWCNTs and polyethylene by melt blending of amine-functionalized nanotubes with PEgMA.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al [9] used maleic anhydride grafted styrene-(ethylene-co-butylene)-styrene copolymer (MA-SEBS) as compatibilizer in thermal studies on ultrahigh molecular mass polyethylene-carbon nanotube composites. Prashantha et al [10] found maleic anhydride grafted polypropylene (PPgMA) to improve the dispersion of MWCNT in polypropylene. By wrapping around MWCNTs, the PPgMA gave higher modulus and strength.…”
Section: Introductionmentioning
confidence: 99%
“…They became the points of higher stress concentrations, thus providing sites for crack initiation [2]. The lower impact energy at higher nanotube content was due to the presence some masterbatch agglomerates in the composites [18] as shown in Fig. 6.…”
Section: Effects Of Mwcnt On the Mechanical Properties Of The Pp/mwcnmentioning
confidence: 99%